The corresponding homogeneous ODE is
[tex]y''+4y'-3y=0[/tex]
with characteristic equation
[tex]r^2+4r-3=0[/tex]
which has roots at [tex]r=-2\pm\sqrt7[/tex], which gives two characteristic solutions
[tex]y_c=C_1e^{(-2+\sqrt7)t}+C_2e^{(-2-\sqrt7)t}[/tex]
For the particular solution, let
[tex]y_p=at^2+bt+c[/tex]
with derivatives
[tex]{y_p}'=2at+b[/tex]
[tex]{y_p}''=2a[/tex]
Substituting into the ODE gives
[tex]2a+4(2at+b)-3(at^2+bt+c)=4t^2+5t+6[/tex]
[tex]-3at^2+(8a-3b)t+(2a+4b-3c)=4t^2+5t+6[/tex]
[tex]\implies a=-\dfrac43\implies b=-\dfrac{47}9\implies c=-\dfrac{266}{27}[/tex]
Then the ODE has general solution
[tex]y(t)=C_1e^{(-2+\sqrt7)t}+C_2e^{(-2-\sqrt7)t}-\dfrac43t^2-\dfrac{47}9t-\dfrac{266}{27}[/tex]